2020
DOI: 10.1038/s41467-020-14961-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding and spatial modelling link diet diversification with distribution homogeneity in European bats

Abstract: Inferences of the interactions between species' ecological niches and spatial distribution have been historically based on simple metrics such as low-resolution dietary breadth and range size, which might have impeded the identification of meaningful links between niche features and spatial patterns. We analysed the relationship between dietary niche breadth and spatial distribution features of European bats, by combining continent-wide DNA metabarcoding of faecal samples with species distribution modelling. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 59 publications
2
44
1
Order By: Relevance
“…Using eDNA metabarcoding, we have shown that R. ferrumequinum diet is much more diversified than previously described by microscopic (Flanders & Jones, 2009; Jones, 1990) and molecular analyses (Alberdi et al., 2020; Aldasoro et al., 2019; Galan et al., 2018). We revealed a broader ecological and taxonomic variety of prey from the order to species levels of taxonomic resolution (519 species; 76% of the taxa affiliated at the species level).…”
Section: Discussionmentioning
confidence: 60%
“…Using eDNA metabarcoding, we have shown that R. ferrumequinum diet is much more diversified than previously described by microscopic (Flanders & Jones, 2009; Jones, 1990) and molecular analyses (Alberdi et al., 2020; Aldasoro et al., 2019; Galan et al., 2018). We revealed a broader ecological and taxonomic variety of prey from the order to species levels of taxonomic resolution (519 species; 76% of the taxa affiliated at the species level).…”
Section: Discussionmentioning
confidence: 60%
“…Newer techniques such as high‐throughput amplicon sequencing (HTAS) can characterize animal diets at a much finer taxonomic resolution than other methods, providing a more comprehensive way to study the entire suite of prey resources consumed by generalist predators (Jusino et al, 2019; Kaartinen et al, 2010; Zeale et al, 2011). Since the advent of these methods, many studies have described the diets of a wide range of taxa (Alberdi et al, 2019, 2020; Piñol et al, 2014; Pompanon et al, 2012; Wray et al, 2018). These types of studies collectively represent an important first step in describing animal diets, especially for those that use a broader diversity of prey resources than other methods that are capable of detecting.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, among the two dominant species (amounting to 91.32% of the captured mosquitoes) C. modestus is more crepuscular than C. pipiens , 95 which might contribute to its absence in the analysed faeces. Moreover, methodological biases in the molecular analyses may have contributed to the absence of C. modestus , namely, (i) the detectability by the primers used (though the species has been found using the same primer in Myotis daubentonii in the Balkans) 96 ; (ii) the lower number of sequences available in the BOLD System and GenBank when compared to C. pipiens (409 sequences available for C. modestus versus 4065 for C. pipiens ); and (iii) taxonomic assignment errors related to the limited number of pairs of bases used ( N = 160) in the faecal samples 97 . Furthermore, the lure used in the mosquito traps mimics human sweat odour and is thus biased towards human or mammal‐selective mosquitoes.…”
Section: Discussionmentioning
confidence: 99%